RNA-Seq Assembly and Differential Transcriptome Analysis of Korean Medicinal Herb var. - Neha Samir Roy; Jung-A Kim; Ah-Young Choi; Yong-Wook Ban; Nam-Il Park; Kyong-Cheul Park; Hee-sun Yang; Ik-Young Choi; Soonok Kim (Genomics & Informatics)
Cirsium japonicum belongs to the Asteraceae or Compositae family and is a medicinal plant in Asia that has a variety of effects, including tumour inhibition, improved immunity with flavones, and antidiabetic and hepatoprotective effects. Silymarin is synthesized by 4-coumaroyl-CoA via both the flavonoid and phenylpropanoid pathways to produce the immediate precursors taxifolin and coniferyl alcohol. Then, the oxidative radicalization of taxifolin and coniferyl alcohol produces silymarin. We identified the expression of genes related to the synthesis of silymarin in C. japonicum in three different tissues, namely, flowers, leaves, and roots, through RNA sequencing. We obtained 51,133 unigenes from transcriptome sequencing by de novo assembly using Trinity v2.1.1, TransDecoder v2.0.1, and CD-HIT v4.6 software. The differentially expressed gene analysis revealed that the expression of genes related to the flavonoid pathway was higher in the flowers, whereas the phenylpropanoid pathway was more highly expressed in the roots. In this study, we established a global transcriptome dataset for C. japonicum. The data shall not only be useful to focus more deeply on the genes related to product medicinal metabolite including flavolignan but also to study the functional genomics for genetic engineering of C. japonicum.